Learning Innovation for the Implementation of Industrial Practices for Construction Engineering and Property in Vocational High School According to the Construction Service Industry Needs - Nugraheni, Natasya Atikasari; Sugandi, R. M; Sutrisno, Sutrisno (Teknologi dan Kejuruan: Jurnal Teknologi, Kejuruan, dan Pengajarannya, 2020)
Abstract: Field Work Practices is practical learning activities to apply, stabilize, and improve the competence of students. These students need teaching materials by utilizing of E-Module with kvisoft flipbook maker application. The development functions for innovation is essential in increasing the readiness of Field Work Practices so that students could carry out Field Work Practices following with the needs of the Construction Services Industry. The development began with the data collection stage followed by product design, design validation, product revision, testing the product, and finishing the product. The results of material expert validation for learning design aspects was 92.19%, 87.5% for learning elements, and learning strategy aspects was 84.38%. The score of media experts for software engineering aspects was 89.58%, and visual communication aspects were 87.5%. The average response score of respondents for elements of the use of teaching materials were 86.04%, parts of the usefulness of teaching materials were 85.94%, and the conformity aspects of teaching materials 84.18%. Overall, the e-module teaching materials for Field Work Practices were good, exciting and very feasible to use as learning teaching materials. Besides, it can improve students' readiness in preparing Field Work Practices